2019
DOI: 10.1108/ajim-01-2019-0002
|View full text |Cite
|
Sign up to set email alerts
|

What drives users’ participation in online social Q&A communities? An empirical study based on social cognitive theory

Abstract: Purpose The purpose of this paper is to examine some drivers of users’ participation in online social question-and-answer (Q&A) communities based on social cognitive theory and then identify the underlying mechanism of this process. Design/methodology/approach This study developed a research model to test the proposed hypotheses, and an online survey was employed to collected data. Totally, 313 valid responses were collected, and partial least squares structural equation modeling was adopted to analyze t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 54 publications
2
41
0
1
Order By: Relevance
“…, 2016). Under the conscious/rational perspective, the positive expectation will increase users' willingness toward continued participation (Bao and Han, 2019). However, in the context of OHC, data from Wang et al.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…, 2016). Under the conscious/rational perspective, the positive expectation will increase users' willingness toward continued participation (Bao and Han, 2019). However, in the context of OHC, data from Wang et al.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…As for the relationships between indirect social support receipt and users' continued behavior, research on social support exchange in disaster has shown that observing social support can increase peoples' expected support, which means the expectation that social support would be provided when needed (Drury et al, 2016). Under the conscious/rational perspective, the positive expectation will increase users' willingness toward continued participation (Bao and Han, 2019). However, in the context of OHC, data from Wang et al (2017) suggested that indirect informational support receipt is negatively associated with users' continued participation, and indirect emotional support receipt is not related to users' continued participation.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Specifically, many researchers have explored the information-sharing motivation, incentive mechanisms, and influential factors that shape the participants' information-sharing behaviors. They applied various theories such as the theory of planned behavior (Lin et al, 2018), social capital theory (Zhang et al, 2017), social cognitive theory (Bao & Han, 2019), social influence theory (Chou et al, 2015), and social exchange theory (Mpinganjira, 2018).…”
Section: Information-sharing Mechanism In Virtual Communitiesmentioning
confidence: 99%
“…Referente à questão 7, quando inquiridos se o motivo principal de compartilhar informação e conhecimento seria uma satisfação pessoal, novamente, a maioria foi positiva: 58,3% concordaram plenamente e 33,3% parcialmente, não havendo discordâncias. Argumenta-se que essa postura pode ser decorrente tanto de valores pessoais que o sujeito incorporou ao longo da vida, como também consequência de um senso desenvolvido de autoeficácia, que é a crença na própria capacidade de realização e construção de conhecimento (BANDURA, 1978;BAO;HAN, 2019).…”
Section: Fatores Egocêntricos E Altruístas Intervenientes No Compartiunclassified